(untitled) (Patan Pragya, 2022)
This paper deals with the protagonist, Siddhartha’s dissatisfaction with his life, mental turmoil, inquisitiveness in knowing his existence and his quest for self-Discovery in the novel Siddhartha. This novel was written by Hermann Hesse and was published in 1922. It was his masterpiece, which shows his journey to the East, the influence of Buddhist philosophy upon him and his autobiographical elements that pave a way for one’s journey to Spiritual knowledge in this physical world. As the novel was written in the First World War years, the search for spiritualism would naturally be the interest of most of Europeans who found Europe devoid of it. So, Hess made his journey to the East (India) in quest of spiritualism as the protagonist of the novel does. One major objective of the research work is to explore different factors that enable Siddhartha to discover his self. Why Siddhartha is in search of self is the research question. Siddharth is in search of self since he is not happy and satisfied with love of his parents and friend and finds his life meaningless and devoid of freedom. Like the writer, Siddhartha comes across a lot of illusions that human beings encounter in their daily life. He passes through multiple vicissitudes and experiences in his life through sufferings and salvation. His such self-actualization with social life and nature ultimately leads him to attain nirvana. Thus, his quest for self-discovery indicates elements of autobiographical elements, existentialism, and self-actualizing tendency which is based on Carl Rogers’ humanistic psychology. As for the theoretical modality, Jean-Paul Sartre’s theory of Existentialism is applied to explore Siddhartha’s search for self, which is like Europeans’ search for self due to devastation made by world war and Siddhartha Guatam’s search for self due to his dissatisfaction with the world.